SUPPORTING THE USE OF RESEARCH EVIDENCE TO INFORM DECISION-MAKING IN CRISIS ZONES - Khalid, Ahmad Firas (My University, 2019)
Many strategies can be used to support the use of research evidence in decision-making. However, such strategies have been understudied in crisis zones, where decision-making may be particularly complex, many factors may influence decision-makers’ use of research evidence, and professional judgements may be particularly relied upon. Using synthesis and qualitative research methods, this dissertation examines the role of research evidence in crisis zones and strategies to support its use in decision-making. First, chapter 2 describes a critical interpretive synthesis, which drew upon a broad body of literature around evidence use in crisis zones to develop a new conceptual framework that outlines strategies that leverage the facilitators and address the barriers to evidence use in crisis zones in four systems, namely the political, health, international humanitarian aid, and health research systems. Second, in chapter 3, the focus narrows, and an embedded qualitative case study design was used to gain a deeper understanding into one of the four identified systems, the political system, and specifically the factors that influenced the use of research evidence in the governmental health policy-development processes for Syrian refugees in Lebanon and Ontario. Finally, in chapter 4, a user testing study design was used to zero-in on decision-makers’ experiences with a particular strategy within the health research system, namely an evidence website focused specifically on topics relevant in crisis zones. This dissertation provides a rich understanding of research evidence use by examining knowledge translation strategies in a setting that has been largely unexplored in the broader KT map: crisis zones. The findings from this thesis point to the need for comprehensive strategies to support evidence use in decision-making that draw upon the existing literature and are adapted for crisis zones, which can occur sequentially or simultaneously within or across the four identified systems.
EVIDENCE-INFORMED DECISION-MAKING IN CRISIS ZONES
Keywords: Health systems research; decision-making; research evidence; crisis zones; CIS; Case study; User testing; LMICs; knowledge translation; evidence aid; Syrian refugee crisis; health policy; Lebanon; Ontario; evidence websites; evidence-informed decision making; critical interpretive synthesis